Mitigation versus competitiveness? Industry ompensation in the European Union Emissions Trading System - Till Köveker; Robin Sogalla (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
Carbon pricing policies are usually combined with compensation for exposed firms to prevent adverse competitiveness effects. In cap-and-trade systems, this carbon cost compensation mostly occurs through free allocation of emission permits. Using an administrative panel of German manufacturing firms, this paper investigates how free allocation in the European Union Emissions Trading System affects firms' competitiveness and their incentives to reduce emissions. Leveraging a reform of free allocation rules in a continuous difference-in-differences design, we find that that a reduction of freely allocated emission permits decreased firms' emission intensity. Our results suggest that this decrease is driven by energy efficiency improvements instead of outsourcing of emission intensive production. On the other hand, we do not find statistically significant effects on firms' employment, sales, value added, investments and exports - indicating that the reduction in free permits did not reduce firms' competitiveness.
Keywords: Q54; Q58; H23; D22; F18; 330; Cap and Trade; Permit Allocation; Industry Compensation; Greenhouse Gas Emissions; Competitiveness; Manufacturing Firms